Role of Host and Temperature on the Feeding and Oviposition Behaviour of Red Pumpkin Beetle Aulacophora foveicollis (Lucas) - Kamal, MM; Uddin, MM; Shajahan, M; Rahman, MM (Progressive Agriculture, 2014)
The research was carried out in the field and laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh during December, 2011 to October, 2012 on the effect of host and temperature on oviposition and food consumption of red pumpkin beetle (RPB), Aulacophora foveicollis (Lucas). Three cucurbitaceous vegetables viz. sweet gourd (BARI Misti Kumra-1, BARI Misti Kumra-2 and Local Misti Kumra), bitter gourd (BARI Karola-1, Taj Karola-88 and Local Karola) and bottle gourd (BARI Lau-3, BARI Lau -4 and Local Lau) were selected to conduct this research. Host plants had the clear role on the feeding of red pumpkin beetle. Due to feeding of A. foveicollis, the highest percentage of weight loss of leaf was recorded from sweet gourd among the selected cucurbits while Local Misti Kumra was found the most preferred host by beetle considering their feeding efficacy compared to other varieties. Results also showed that temperature had a profound effect on the oviposition and food consumption by A. foveicollis while 30oC was the optimum temperature both for oviposition and food consumption for all selected cucurbits and their varieties. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19099 Progress. Agric. 24(1&2): 53 - 60, 2013